2016
DOI: 10.1111/gfs.12266
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sampling and storage technique, and duration of storage, on the composition of fresh grass when analysed using near‐infrared reflectance spectroscopy

Abstract: The objective of this study was to examine the effect of sampling technique (pluck or cut), storage duration (immediate analysis, 24‐h or 48‐h), storage temperature (ambient or chilled) and storage conditions (air present, air excluded or breathable) on the composition of fresh grass sampled from a sward managed to simulate grazing. Treatments were repeated across four sampling dates, with grass samples stored in grip seal bags prior to analysis using near‐infrared reflectance spectroscopy. Grass sampled by ‘p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The analysis of other pasture nutrient concentrations is typically done in the laboratory after being sent in the postal system, with results received after the grazing event. Unlike ensiled forages both oxidative degradation of carbohydrates and hydrolysis of peptides continues post-harvest in fresh grass (Binnie et al, 1997;Dale et al, 2016). Dale et al (2016) suggested nutrient analysis should occur within 24 h to minimize degradation to plant material and changes in nutrient concentrations.…”
Section: Discussion Precision Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of other pasture nutrient concentrations is typically done in the laboratory after being sent in the postal system, with results received after the grazing event. Unlike ensiled forages both oxidative degradation of carbohydrates and hydrolysis of peptides continues post-harvest in fresh grass (Binnie et al, 1997;Dale et al, 2016). Dale et al (2016) suggested nutrient analysis should occur within 24 h to minimize degradation to plant material and changes in nutrient concentrations.…”
Section: Discussion Precision Monitoringmentioning
confidence: 99%
“…Unlike ensiled forages both oxidative degradation of carbohydrates and hydrolysis of peptides continues post-harvest in fresh grass (Binnie et al, 1997;Dale et al, 2016). Dale et al (2016) suggested nutrient analysis should occur within 24 h to minimize degradation to plant material and changes in nutrient concentrations. This is unlikely to occur within a small country such as the UK, let alone larger countries, where the distance to analytical laboratories may be greater.…”
Section: Discussion Precision Monitoringmentioning
confidence: 99%
“…Alomar et al [81] concluded that reflectance NIRS could accurately predict the compositional components, including DM (R 2 = 0.99, SE = 6.5 g kg −1 ) (SE = standard error) and CP (R 2 = 0.91, SE = 18.4 g kg −1 ), of a variety of fresh grass swards in Southern Chile. Dale et al [82] developed fresh grass NIRS calibrations to investigate optimum sampling and storage techniques on Irish PRG dominant pastures and reported R 2 values of 0.92 (SE = 0.95 g kg fresh weight −1 ), 0.90 (SE = 0.543 g kg fresh weight −1 ) and 0.79 (SE = 0.622 g kg fresh weight −1 ) for DM, N and WSC, respectively. Lobos et al [83] reported good prediction performance (R 2 ≥ 0.84) for fresh grass NIRS analysis for parameters DM (RMSE = 1.13%) and CP (RMSE = 2.22%), in comparison with low prediction performance (R 2 ≤ 0.78) for DMD (RMSE = 2.41%), OMD (RMSE = 2.61%), and WSC (RMSE = 0.06%) in Chilean permanent pasture.…”
Section: Grass Quality Analysis By Means Of Near Infrared Spectroscopymentioning
confidence: 99%
“…New tools and sources of information for biomass and nutrient composition measurements are being developed to help quantify temporal and spatial changes in herbage in real-time to provide more timely information for enhanced land management [10][11][12]. For perishable plant material, such as grass, the implementation of real-time near-infrared spectroscopy (NIRS) is beneficial given that changes in nutrient concentrations can occur within 24 h of harvesting [13]. Bell et al [12] used real-time NIRS combined with a measure of herbage production (e.g., herbage per hectare and its height) to show that grazing pastures of a mean height of below seven centimetres result in a significantly reduced concentration of crude protein and digestibility, which may be detrimental to the productivity of grazing animals.…”
Section: Introductionmentioning
confidence: 99%